The uncanny house - Baccin, Andrea; Marotta, Ilaria (Sorry Press, 2024)
In the wake of the widespread leitmotiv that nourished literary fantasy, fairy tales, horror stories and artistic creation alike since the early 19th century, The Uncanny House investigates the sense of unheimlich within the rooms of the Rome apartment where Johann Wolfgang von Goethe lived between 1786 and 1788. It is a place that provides an especially favored locus for uncanny disturbances: its apparent domesticity, its residue of nostalgia and its role as the last and most intimate shelter of private comfort are sharpened by the contrast of empty spaces, crevices, chimeras, ghosts, alien spirits, time shifts and voices that creep in. Through the work of eighteen international artists, the house thus becomes a place where ambiguities, obsessive thoughts and the neurotic dimensions of the human sphere become apparent
Impressum: The Uncanny House book is published on the occasion of the exhibition "The Uncanny House", Museum Casa di Goethe, Rome, March 28 - September 01, 2024
Keywords: Franceschini, Anna -- 1979-; Serapinas, Augustas -- 1990-; Schneider, Gregor -- 1969-; Vascellari, Nico -- 1976-; Altmann, Mathis -- 1987-; Goethe, Johann Wolfgang von -- 1749-1832; De Luca, Tomaso -- 1988-; Budor, Dora -- 1984-; Whiteread, Rachel -- 1963-; Serpas, Ser -- 1995-; Giller, Lenard -- 1997-; Matranga, Mélanie -- 1985-; Silva, Giovanna -- 1980-; Casa di Goethe; Das Unheimliche; Kunst; Wohnung; Rezeption; Rom; Sorry Press; Wiegand von Hartmann; Moritz Wiegand; Goethe; Italienreise; Goethes Reise; Museum in Rom; The Uncanny House; Das unheimliche Haus; Ausstellungskatalog -- Casa di Goethe -- 28.03.2024-01.09.2024 -- Rom; Ausstellungskatalog -- Museum Casa di Goethe -- 28.03.2024-01.09.2024 -- Rom; Bildband